The artistic morphology of the absurdist drama (from Kozma Prutkhov to Daniel Kharms) - Миловидов, Виктор (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
The article adresses Russian absurdist drama in the context of disourse analysis, showing the procedures of semantisation as being based not on the immanent textual characteristics, but on the outward reality and literary tradition.